Fabrication of bFGF/polydopamine-loaded PEEK implants for improving soft tissue integration by upregulating Wnt/β-catenin signaling. Issue 4 (April 2023) - Wang, Xiaohu; Ma, Ning; Feng, Li; Shen, Mingkui; Zhou, Yaqi; Zhang, Xinan; Huang, Ruichao; Zhou, Li; Ji, Shanfeng; Lou, Yongli; Zhu, Zhi
Abstract: The difficulties associated with polyetheretherketone (PEEK) implants and soft tissue integration for craniomaxillofacial bone repair have led to a series of complications that limit the clinical benefits. In this study, 3D printed multi-stage microporous PEEK implants coated with bFGF via polydopamine were fabricated to enhance PEEK implant-soft tissue integration. Multistage microporous PEEK scaffolds prepared by sulfonation of concentrated sulfuric acid were coated with polydopamine, and then used as templates for electrophoretic deposition of bFGF bioactive factors. Achieving polydopamine and bFGF sustained release, the composite PEEK scaffolds possessed good mechanical properties, hydrophilicity, protein adhesion properties. The in vitro results indicated that bFGF/polydopamine-loaded PEEK exhibited good biocompatibility to rabbit embryonic fibroblasts (REF) by promoting cell proliferation, adhesion, and migration. Ribonucleic acid sequencing (RNA-seq) revealed that bFGF/polydopamine-loaded PEEK implants significantly upregulated the expression of genes and proteins associated with soft tissue integration and activated Wnt/β-catenin signaling in biological processes, but related expression of genes and proteins was significantly downregulated when the Wnt/β-catenin signaling was inhibited. Furthermore, in vivo bFGF/polydopamine-loaded PEEK implants exhibited excellent performance in improving the growth and adhesion of the surrounding soft tissue. In summary, bFGF/polydopamine-loaded PEEK implants possess soft tissue integration properties by activating the Wnt/β-catenin signaling, which have a potential translational clinical application in the future. Highlights: PEEK implants were modified by structural porosification and surface activation simultaneously. Modificated PEEK implants had good cell biocompatibility. The RNA-seq revealed that Wnt/β-catenin signaling was activated by modificated PEEK implants. BFGF/polydopamine-loaded PEEK implants improved soft tissue integration properties.